DIFFERENCES BETWEEN YOUNG (13-14 YEARS OF AGE) WATER POLO PLAYERS SELECTED AND NOT SELECTED TO THE NATIONAL TEAM - Igor Štirn (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Young water polo players at age 13 to 14 years were examined once a year in a four- year period using three morphological and eight specific skill tests: body height and mass, vital capacity, swimming at distances 5, 25 and 200 meters, swimming 4x5 meters with changing directions, ball dribbling, vertical jump and reach, vertical eggbeater kick and velocity of a throw at the goal. From the sum of 139 players tested, a group of 73 non-selected and of 66 selected players to the national team (U16, wider selection) were formed and checked for differences. Differences in all observed variables (except body mass) were found between the groups (P<0.05). One significant discriminant function was revealed (canonical R = 0.52) and the accounted variance was 100 %, P = 0.000. The variables that most differentiated the groups were swimming tests at distances of 25 and 200 meters, followed by vertical-egg beater kick and throwing velocity, while morphological variables differentiated the groups least.